Reflections on the use of hypotheses in ethnobotany: A response to Leonti et al. (2020) - Ferreira Júnior, Washington Soares; Albuquerque, Ulysses Paulino; Medeiros, Patrícia Muniz (Ethnobotany Research and Applications, 2021)
In this article, we examine the review by Leonti et al. (2020) on the use of hypotheses in ethnobotany and we argue that the authors presented two main argumentative deficiencies on their analysis: superficiality and epistemological exclusivism. We discussed the main criticisms of the diversification hypothesis, the utilitarian redundancy model and the availability hypothesis and reinforced the importance of using ecological and evolutionary scenarios to understand the relationship between people and plants.